Citrate-capped gold nanoparticles for the label-free detection of ubiquitin C-terminal hydrolase-1. Issue 4 (17th December 2014) - Agarwal, Srishti; Mishra, Priyanka; Shivange, Gururaj; Kodipelli, Naveena; Moros, María; de la Fuente, Jesús M.; Anindya, Roy
Abstract : Ubiquitin C-terminal hydrolase-1 (UCH-L1) is a specific neuronal endoprotease that cleaves the peptide bond between ubiquitin molecules. Abstract : Ubiquitin C-terminal hydrolase-1 (UCH-L1) is a specific neuronal endoprotease that cleaves the specific peptide bond between ubiquitin molecules. UCH-L1 is released in serum and cerebrospinal fluid after severe brain injury and is considered to be an important biomarker of brain injury. A common polymorphism of UCH-L1 (S18Y) is also linked to a reduced risk of Parkinson's disease. In addition to its function in neuronal tissues, UCH-L1 may also play a part in the progression of certain non-neuronal cancers. UCH-L1 is highly expressed in primary lung tumors and colo-rectal cancers, suggesting a role in tumorigenesis. We report here the development of a sensitive and accurate UCH-L1 assay based on the surface plasmon resonance (SPR) absorbance of gold nanoparticles. We created a unique UCH-L1 substrate containing a ubiquitin molecule with two terminal thiol groups. This UCH-L1 substrate interacted with gold nanoparticles via the terminal thiol groups and induced clustering of the nanoparticles, which was detected by SPR absorbance at 650 nm. UCH-L1 proteolytically cleaved the substrate and the clustered gold nanoparticles were dispersed and could be detected by a shift in the SPR absorbance to 530 nm. This change in absorbance was proportional to the concentration of UCH-L1 and can be used for the quantification of functional UCH-L1. The currently available fluorescence-based UCH-L1 assay is affected by a high background signal and a poor detection limit, especially in the presence of serum. The assay reported here can detect concentrations of UCH-L1 as low as 20 ng ml −1 (0.8 nM) and the presence of serum had no effect on the detection limit. This assay could be adapted for the rapid determination of the severity of brain injury and could also be applied to high-throughput screening of inhibitors of UCH-L1 enzymatic activity in Parkinson's disease and cancer.